Recognising Echoism As A Phenomenon In Existential Therapy: A Daseinsanalytic Hermeneutic Approach (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
In my paper published in this journal (27.2) in 2015, I asked 'Is there a place for echoism in existential analysis?'. In the intervening years I have carried out research which I have recently published in my book Echoism: The Silenced Response to Narcissism (Savery, 2018). The research is based upon my attempts to understand individuals whom I have met in my consulting room over a period of seven years, who find themselves repeatedly in relationships with narcissists or who are recovering from narcissistic parenting. In order to understand the particular ways in which such individuals relate and to try to find a way to best help them in therapy, I have used as my primary resource the experience of being with such individuals whom I have, for reasons I go on to explain, come to call echoists. While the existential schools of therapy generally have good reasons for avoiding labels – I argue here why the application of a name is important if we are to recognize and help such individuals, if and when they appear in our consulting rooms.
Keywords: Echoism; narcissism; echoist; narcissist; Echo; Ovid; myth; reluctant philosopher; Daseinsanalysis; hermeneutic; Holzhey-Kunz; Sartre; Being; The Look